THE IMPACT OF SOCIAL MEDIA AND VLOGGING ON SPEAKING SKILL DEVELOPMENT - Teshaboyeva Nafisa Zubaydulla qizi; Ibragimova Shahrizoda Ravshan qizi (Ustozlar uchun, 2025)
In recent years, social media and vlogging have become powerful tools not only for entertainment and communication but also for personal development. One of the most significant areas of growth is speaking skill enhancement, especially among young people. This article explores how platforms such as YouTube, TikTok, and Instagram influence users’ verbal communication, fluency, pronunciation, and public speaking confidence. The research focuses particularly on the context of Uzbekistan, where social media usage is rapidly increasing among students and vloggers. The study uses a mixed-methods approach, combining literature review with local observations and examples to show the practical impact of digital platforms on speaking skills. The findings suggest that vlogging and social media help learners become more confident, expressive, and fluent in their speech. However, the article also addresses the potential drawbacks, such as reliance on informal language or loss of grammatical accuracy. The paper concludes with recommendations for how educators and students in Uzbekistan can use social media as a tool for language and communication skill development.